Human and physical geography and the question of space - Kevin Cox (Belgeo)
Human and physical geography share a concern with the implications of spatial arrangement for process and hence for differentiation over the earth’s surface. In human geography, its explanatory role is crucial to (sub-) disciplinary awareness. In physical geography this is not the case. In the first place, this is a result of prevailing views of space: space as relative in human geography and as relational in physical geography. In human geography, space exists because objects exist and can exercise effects; in physical geography space is constitutive of objects, so that the idea of separate spatial effects is meaningless. This might seem to have to do with the fundamental nature of objects: people exercise choice in a way that packets of air cannot. What this fails to recognize is that choice is always exercised under particular social conditions; those of capitalism seem to impose a separation of objects from each other and from space that is wholly illusory.